2016
DOI: 10.1007/s00253-016-7368-0
|View full text |Cite
|
Sign up to set email alerts
|

Deammonification for digester supernatant pretreated with thermal hydrolysis: overcoming inhibition through process optimization

Abstract: The thermal hydrolysis process (THP) has been proven to be an excellent pretreatment step for an anaerobic digester (AD), increasing biogas yield and decreasing sludge disposal. The goal of this work was to optimize deammonification for efficient nitrogen removal despite the inhibition effects caused by the organics present in the THP-AD sludge filtrate (digestate). Two sequencing batch reactors were studied treating conventional digestate and THP-AD digestate, respectively. Improved process control based on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 49 publications
0
19
2
Order By: Relevance
“…Another potential advantage of feed dilution is that the concentration of sCOD leaving the digester is lower, and this could reduce inhibition of sidestream processes. For example, deammonification has been used to treat return liquors from THP‐AD systems and components in the filtrate have been shown to be inhibitory (Figdore et al., ; Zhang et al., ). Figdore et al.…”
Section: Research Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another potential advantage of feed dilution is that the concentration of sCOD leaving the digester is lower, and this could reduce inhibition of sidestream processes. For example, deammonification has been used to treat return liquors from THP‐AD systems and components in the filtrate have been shown to be inhibitory (Figdore et al., ; Zhang et al., ). Figdore et al.…”
Section: Research Implicationsmentioning
confidence: 99%
“…() suggested that the inhibitory compounds were associated with the sCOD fraction, while Zhang et al. () suggested that colloidal and particulate COD fractions were associated with inhibition. Figdore et al.…”
Section: Research Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pilot simulated the BNR system at Blue Plains with the difference that an aggressive aerobic SRT (1 to 5 days) was used under transient anoxia and anammox granules were bioaugmented. Therefore, this system can be seen as a hybrid system with a small fraction of anoxic ammoniumoxidizing granules; (4) Sidestream sludge was obtained from a sidestream deammonification pilot at Blue Plains (Zhang et al, 2016). The sidestream pilot plant was a sequencing batch reactor, which was treating centrate from the Alexandria Sanitation Authority.…”
Section: Methodsmentioning
confidence: 99%